FACTORS ASSOCIATED WITH END OF LIFE TRANSITION FOR OLDER ADULTS LIVING AT HOME: ANALYSIS OF CARERS' POST-BEREAVEMENT SURVEY. Issue 1 (1st March 2015) - Evans, CJ; Bone, AE; Yi, D; Wei, G; Gomes, B; Maddocks, M; Sleeman, KE; Wright, J; Mc Crone, P; Higginson, IJ; ,
Abstract : Introduction: Transfer to hospital in the last weeks of life is common for older adults. It is imperative to better understand factors associated with transition to enable older people to remain in their usual place of care. Aim(s) and method(s): To explore possible determinants of transition from home to institutional care settings in last weeks of life. Post-bereavement survey of carers to people aged over 75 who died in 2012 in the South of England (n=883). Main outcome is death at home versus hospital/care home (hospice deaths excluded) for decedents whose usual place of care was home. Exploration of socio-demographic factors and illness factors using multivariate modified Poisson regression. Results: 235 decedents spent most of the last 3 months of life at home. The majority died from non-malignant conditions (71.9%) with mean age 86 years. 51.1% died at home and 48.9% transitioned in the last 3 months to a hospital (44.7%) or care home (4.3%). Death outside usual place of care was independently associated with increasing age (85–90 years [PR=3.4; 95% CI 1.9–6.1] compared with 75–80 years), and severity of breathlessness (PR=1.9; 95% CI 1.2–3.4) and difficulty communicating (PR=2.0; 95% CI 1.5–2.8). Conclusion(s): Transition to hospital at the end of life is common for older adults living at home. Transition occurs most frequently for the oldest old and those with severe symptoms of breathlessness and difficulty communicating. To reduce reliance on hospital care at the end of life requires timely services responsive to increasing symptom distress and wider anticipation of end of life for adults of advanced age.